DESIGN AND EXPERIMENTAL ANALYSIS OF A NONLINEAR ULTRAHARMONIC VIBRATOR EXCITER - WANG ChengJun; SHANG ChenChen; ZHANG YuPing (Jixie qiangdu)
Aiming at the problem that the vibration frequency of conventional vibration exciter is small and can not realize the resonance of high stiffness components, Based on the superharmonic vibration characteristics of nonlinear vibration system, designed a nonlinear ultraharmonic vibrator exciter composed of 3 linear springs and 3 nonlinear springs. Established the dynamic model of the nonlinear ultraharmonic vibrator exciter, solved the nonlinear vibration amplitude-frequency characteristic equation by using the multi-scale method, and analyzed the theoretical feasibility of the vibration exciter to achieve third ultraharmonic resonance. Analyzed effects of excitation force amplitude, nonlinear stiffness coefficient and nonlinear damping coefficient on nonlinear vibration amplitude-frequency response. Carried out dynamic simulation of nonlinear ultraharmonic vibrator exciter by using ADAMS, and carried out the vibration experiment of the nonlinear ultraharmonic vibrator exciter. The results show that under the adjustment of the nonlinear spring, the exciter can achieve third ultraharmonic resonance, which verifies the rationality of the design of the nonlinear super-resonant exciter.